Sex differences in everyday risk-taking behavior in humans - Pawlowski, B; Atwal, R; Dunbar, R (Evolutionary Psychology, 2008)
Sexual selection theory predicts that males will tend to behave in ways that are more risky than females. We explored this in humans by studying two everyday situations (catching a bus and crossing a busy road). We show that humans are competent otpimizers on such tasks, adjusting their arrival times at a bus stop so as to minimize waiting time. Nonetheless, single males pursue a more risky strategy than single females by cutting waiting times much finer. Males are also more likely than females to cross busy roads when it is risky to do so. More importantly, males are more likely to initiate a crossing in high risk conditions when there are females present in the immediate vicinity, but females do not show a comparable effect in relation to the number of males present. These results support the suggestion that risk-taking is a form of "showing off" used as mate advertisement.